Magnesium ion secondary battery
By utilizing a separator with tailored permeability and thickness, and a magnesium alloy with a eutectic crystal structure containing lithium, the magnesium ion secondary battery addresses internal short circuit and overvoltage issues, achieving improved performance and energy density.
Patent Information
- Application Number
- JP2023169646
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Magnesium ion secondary batteries using magnesium alloys in the eutectic state face challenges with internal short circuits and increased overvoltage due to the exposure of electrochemically active surfaces at grain boundaries, leading to concentrated current and tower-shaped magnesium deposition.
The magnesium ion secondary battery employs a separator with specific ISO permeability (110
This configuration effectively suppresses internal short circuits and reduces overvoltage, enhancing the charge/discharge characteristics and maintaining a high volume energy density comparable to lithium-ion batteries.
Smart Images

Figure 2025059515000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnesium ion secondary battery. [Background technology]
[0002] In recent years, environmental problems have become serious issues. Therefore, natural energy power generation is desired from the viewpoint of environmental burden. However, natural energy has an unstable energy supply, and once generated electrical energy needs to be stored. Therefore, there is a demand for high-capacity power storage devices that can store such large amounts of electrical energy.
[0003] Currently, lithium ion secondary batteries and magnesium ion secondary batteries are known as power storage devices (see, for example, Patent Document 1). Among them, magnesium ion secondary batteries have attracted attention as batteries that are expected to have high energy density because the carrier is a divalent magnesium ion. In addition, magnesium metal is more stable in air than lithium metal and has about 1.5 times the theoretical capacity per volume, so there is a demand for practical use of magnesium metal as a metal secondary battery using the negative electrode.
[0004] However, in the hexagonal close-packed (hcp) crystal structure of magnesium, the (0001) plane, which is the bottom surface, is electrochemically inactive and does not exhibit reversible dissolution-precipitation reactions during charging and discharging, making it difficult to put magnesium-ion secondary batteries into practical use.
[0005] Therefore, Patent Document 2 describes that by including lithium in a magnesium alloy, a eutectic state is formed in which two phases, a body-centered cubic lattice structure and a hexagonal close-packed structure, coexist. Since the body-centered cubic lattice structure has a lower atomic packing rate than the hexagonal close-packed structure, it is believed that insertion and desorption of magnesium ions into the bulk is smooth, resulting in improved charge and discharge characteristics. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2020 / 013328 [Patent Document 2] Patent No. 5304961 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in materials in which two phases, a body-centered cubic lattice structure and a hexagonal close-packed structure, coexist, different crystal structures are mixed, and therefore electrochemically active surfaces are partially exposed near the grain boundaries on the electrode surface, which correspond to the areas where different crystal structures are adjacent. When a part of the active surface is exposed, the current concentrates at that location, and the electrolytically deposited magnesium deposits in a tower shape, penetrating the separator and causing an internal short circuit. This is a problem that does not occur with other magnesium metal anodes, and is a major disadvantage of the above material compared to other magnesium metal anodes.
[0008] In order to solve the above problem, the present inventors have considered increasing the thickness of the separator. However, increasing the thickness of the separator increases the resistance. The increased resistance increases the overvoltage during charging and discharging, and as a result, when the above negative electrode is used as a battery, an internal short circuit occurs and the overvoltage increases.
[0009] The present invention has been made in consideration of the above, and aims to provide a magnesium ion secondary battery that can suppress the occurrence of internal short circuits and reduce overvoltage when a eutectic magnesium alloy is used as a negative electrode, which is an electrochemically active material. [Means for solving the problem]
[0010] In order to solve the above-described problems and achieve the object, a magnesium ion secondary battery according to the present invention, from a first perspective, includes a positive electrode, a negative electrode having a magnesium layer made of a eutectic magnesium alloy, and a separator, and in the separator, the ISO air permeability W (mL / m 2 ·Pa·s) satisfies 110 < W < 180, and the film thickness X (μm) satisfies 300 < X < 500.
[0011] In addition to the first perspective, a magnesium ion secondary battery according to the present invention, from a second perspective, the magnesium alloy has a crystal structure in which a hexagonal close-packed structure and a body-centered cubic structure are in a eutectic state.
[0012] In addition to the first to second perspectives, a magnesium ion secondary battery according to the present invention, from a third perspective, the magnesium alloy contains lithium in a range of 6% by weight or more and 10.5% by weight or less.
Advantages of the Invention
[0013] According to the present invention, when a eutectic magnesium alloy is used as a negative electrode which is an electrochemically active material, the occurrence of internal short circuit can be suppressed and the overvoltage can be reduced.
Brief Description of the Drawings
[0014] [Figure 1] FIG. 1 is an exploded perspective view for explaining the configuration of a magnesium ion secondary battery according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing X-ray diffraction patterns by the X-ray diffraction method of Example 1, Comparative Example 1, and Comparative Example 2. [Diagram 3] FIG. 3 is a diagram showing the CV measurement results of Example 1, Comparative Example 1, and Comparative Example 2.
Embodiments for Carrying Out the Invention
[0015] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the following description. In addition, various modifications and improvements can be made to the embodiments, and such modifications and improvements can also be included in the present invention.
[0016] The magnesium ion secondary battery of the present invention includes a positive electrode, a separator, a negative electrode, an electrolyte, and an exterior body that contains them. The positive electrode and the negative electrode are arranged so that their active materials face each other, and a separator is present between the positive electrode and the negative electrode.
[0017] (Embodiment) 1 is an exploded perspective view for explaining the configuration of a magnesium ion secondary battery according to one embodiment of the present invention. Magnesium ion secondary battery 1 includes case 110, leaf spring 111, positive electrode current collector 112, positive electrode composite layer 113, separator 114, negative electrode 115, gasket 116, and cap 117. Positive electrode current collector 112 and positive electrode composite layer 113 form positive electrode 118.
[0018] In the magnesium ion secondary battery 1, the case 110 and the cap 117 are fixed by caulking or the like, and the inside is filled with a nonaqueous electrolyte. The magnesium ion secondary battery 1 is liquid-tightly sealed by the case 110, the gasket 116, and the cap 117. In addition, the positive electrode current collector 112, the positive electrode composite layer 113, the separator 114, and the negative electrode 115 are biased toward the cap 117 by the leaf spring 111. This keeps the respective members in close contact with each other.
[0019] (positive electrode) According to this embodiment, a positive electrode for a magnesium secondary battery is provided that includes at least positive electrode current collector 112 and positive electrode mixture layer 113 provided on one or both sides of positive electrode current collector 112.
[0020] Although there is no particular limitation on the material constituting the positive electrode current collector 113, it is preferable to use a metal. Specific examples include copper, aluminum, nickel, stainless steel, titanium, and other alloys. Among them, aluminum is preferable from the viewpoint of electronic conductivity and battery operating potential.
[0021] Examples of the binder used in the positive electrode composite layer 113 include polyethylene, polypropylene, ethylene propylene terpolymer, butadiene rubber, styrene butadiene rubber, butyl rubber, polytetrafluoroethylene, poly(meth)acrylate, polyvinylidene fluoride, polyethylene oxide, polypropylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, and the like, or a mixture thereof.
[0022] Positive electrode active materials include MgCo2O4, MgFeSiO4, S, MnO2, Mo6S8, V2O5, etc. In order to improve electronic conductivity, the positive electrode active material may contain, for example, conductive carbon powder such as graphite or carbon black, carbon nanotubes, carbon nanofibers, graphene, or a mixture thereof.
[0023] (Negative electrode) According to this embodiment, a negative electrode for a magnesium secondary battery is provided that includes at least a negative electrode current collector and a magnesium metal material provided on one or both sides of the negative electrode current collector as the negative electrode 115. Also, the negative electrode current collector does not need to be used.
[0024] There is no particular limitation on the material constituting the negative electrode current collector, but it is preferable to use a metal. Specific examples include copper, aluminum, nickel, stainless steel, titanium, and other alloys. Among them, copper is preferable from the viewpoint of electronic conductivity and battery operating potential.
[0025] The magnesium metal material is a magnesium metal alloy containing at least 6% and at most 10.5% lithium by weight.
[0026] The magnesium metal material is a magnesium metal alloy negative electrode in a eutectic state. In particular, the magnesium metal alloy negative electrode is preferably a eutectic state in which the crystal structure is a hexagonal close-packed (hcp) structure and a body-centered cubic (bcc) structure. More preferably, the lithium content is in the range of 6% by weight to 10.5% by weight. The reason why the negative electrode according to the present embodiment is preferable is that the bcc structure has a lower atomic packing rate than the hcp structure, so that the insertion and desorption of magnesium ions into the bulk is performed smoothly, resulting in improved charge and discharge characteristics. On the other hand, if a negative electrode other than the negative electrode according to the present embodiment is used, it is difficult to insert and desorb magnesium ions into the bulk, and good charge and discharge characteristics cannot be obtained. In this specification, the eutectic state includes a hypoeutectic state and a hypereutectic state, and indicates that two or more types of crystal structures can be confirmed.
[0027] The magnesium metal material is a magnesium metal alloy negative electrode in which, in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα radiation, in addition to a peak derived from the hcp structure, a peak derived from the bcc structure and assigned to the (220) plane exists in the 2θ range of 65° to 66°.
[0028] (electrolyte) The magnesium salt contained in the non-aqueous electrolyte may be one or a mixture of two or more selected from the group consisting of MgCl2, MgBH4, Mg(NO3)2, Mg(TFSI)2, Mg(SO2CF3)2, Mg(BF4)2, Mg(CF3SO3)2, Mg(PF6)2, etc., but is not necessarily limited to these.
[0029] The non-aqueous solvent contained in the non-aqueous electrolyte is not particularly limited. For example, it may be one or a mixture of two or more solvents selected from dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), methyl propionate, methyl acetate, methyl formate, methyl butyrate, dioxolane, 2-methyltetrahydrofuran, tetrahydrofuran, dimethoxyethane, γ-butyrolactone, acetonitrile, benzonitrile, diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme), tetraethylene glycol dimethyl ether (tetraglyme), sulfolane, etc.
[0030] (Separator) Separator 114 has an ISO air permeability W (mL / m 2 ·Pa·s) (hereinafter referred to as "air permeability") that satisfies 110 < W < 180, and the separator film thickness X (μm) satisfies 300 < X < 500. By using separator 114 that satisfies the above range, even when a eutectic magnesium metal negative electrode is used, it is possible to suppress an internal short circuit caused by magnesium electrodeposited in a tower shape, and since the ionic conductivity is improved, it is possible to suppress the overvoltage.
[0031] Here, when the air permeability W is 110 or less, the ionic conductivity becomes poor and the overvoltage increases. On the other hand, when the air permeability W is 180 or more, the strength of the separator becomes brittle and it no longer functions as a separator. Also, when the film thickness X is 300 or less, magnesium electrodeposited in a tower shape penetrates the separator and causes an internal short circuit. On the other hand, when the film thickness X is 500 or more, the resistance component increases and the overvoltage becomes large. Therefore, in order to suppress internal short circuits, which are a problem when using eutectic magnesium, a separator with a thickness that satisfies the above range is required, and in order to improve ionic conductivity and suppress overvoltage, it is necessary to use a separator with an air permeability within the above range.
[0032] An example of a separator that satisfies the above-mentioned air permeability requirement is a glass filter having the above-mentioned thickness, but is not limited thereto.
[0033] The present invention is a groundbreaking invention that can prevent internal short circuits caused by magnesium electrodeposited in a tower shape, which is the reason why eutectic magnesium alloys have not been widely adopted until now, and suppresses an increase in overvoltage. In addition, in conventional magnesium ion secondary batteries, the thickness of the separator has not been set within the above range due to concerns that it may reduce the volumetric energy density, which is an advantage of magnesium ion secondary batteries. However, by setting the air permeability and thickness as in the present invention, it is possible to suppress overvoltage and realize a battery that can ensure a sufficiently high volumetric energy density, even compared to current lithium ion batteries that are in practical use. The present invention provides unexpected effects of the separator and negative electrode.
[0034] In this specification, when the separator has multiple layers or fillers, the film thickness refers to the thickness of the separator including these layers and fillers, and the air permeability refers to the value measured for the entire separator. EXAMPLES
[0035] The present invention will be described in more detail below by way of examples, but the present invention is not limited to the following examples in any way.
[0036] [Effects of lithium-containing magnesium] Example 1 <How to make test batteries> A magnesium alloy containing 9 wt% lithium as the working electrode (hereinafter referred to as Li9), pure magnesium metal (manufactured by Nilaco Corporation) as the reference electrode, a platinum disk electrode (manufactured by EC Frontier Co., Ltd.) as the counter electrode, and an electrolyte obtained by adding LiBH4 as an additive to Mg(TSFA)2 / G2 (Diethyleneglycol dimethyl ether) were used to fabricate a test battery.
[0037] <Measurement of X-ray diffraction pattern> An X-ray diffraction pattern was obtained by X-ray diffraction measurement using Cu-Kα rays. The conditions for the X-ray diffraction measurement were as follows: measurement range: 2θ / θ = 10° to 70°, scanning speed: 2 / min, tube voltage: 40 V, tube current: 20 mA.
[0038] <CV measurement test> A CV (Cyclic Voltammetry) measurement test was performed on the test battery using a three-electrode beaker cell (manufactured by EC Frontier Co., Ltd.). The measurement conditions were as follows: voltage range: -0.5 V to 0.5 V, scanning speed: 5 mV / sec, measurement temperature: room temperature (25°C).
[0039] (Comparative Example 1) It is the same as Example 1 except that pure magnesium was used as the working electrode.
[0040] (Comparative Example 2) It is the same as Example 1 except that a magnesium alloy containing 10 wt% copper (hereinafter referred to as Cu10) was used as the working electrode.
[0041] The measurement results of the X-ray diffraction pattern are shown in Fig. 2. In the test battery using Li9, which is the working electrode used in Example 1, a peak P1 attributed to the (0002) plane existing near 34° (2θ), a peak P2 attributed to the (101(-)0) plane existing near 36°, and a peak P3 attributed to the (220) plane existing in the range of 65° or more and 66° or less, which is derived from lithium substitution, can be confirmed. On the other hand, in Comparative Examples 1 and 2, a peak P attributed to the (0002) plane existing near 34°11 , P 21 , and the peak P which is located near 36° and belongs to the (101(-)0) plane. 12 , P 22 Only the peak attributable to the (220) plane, which is derived from lithium substitution and exists in the range of 65° to 66°, was confirmed.
[0042] The CV measurement results are shown in Figure 3. From the CV measurement results, it was confirmed that Example 1 had a current value approximately 1.5 times higher than that of working electrodes using other elements and magnesium without element substitution (pure magnesium metal and Cu10).
[0043] [Effect of air permeability and film thickness] <Measurement method> The air permeability W of the separator was measured as follows. The separator was measured for ISO air permeability (mL / m) in an atmosphere of 25°C using an Oken air permeability meter (EGO-1T, manufactured by Asahi Seiko Co., Ltd.) in accordance with JIS P-8117:2009. 2 ·Pa·s) was measured. The thickness X of the separator was measured as follows: the battery was disassembled, the separator was removed and washed with an organic solvent such as DMC, the separator was dried, and the thickness of the separator was measured at three points. The maximum thickness measured was taken as the thickness X. The air permeability W and the thickness X can be adjusted to fall within the above ranges by adjusting the blending ratio of the raw materials, the stretching ratio, the heat setting conditions, and the like during the production process.
[0044] <Constant current test> In the constant current test, we compared the overvoltage when Mg metal was used as the electrode. The measurement conditions were 10 mA / cm 2 The test was conducted by charging for one hour and discharging for one hour for 100 cycles at room temperature (25°C).
[0045] <Internal short circuit> The presence or absence of an internal short circuit was judged as follows: the overvoltage after the first cycle was taken as 100%, and the rate of change in overvoltage after 100 cycles relative to the overvoltage after the first cycle was calculated. Cells with a calculated rate of change in overvoltage of less than 20% were judged to have an internal short circuit, and cells with a rate of change of 20% or more were judged to have no internal short circuit.
[0046] <Overall rating> A cell in which the overvoltage after 100 cycles was less than 1.0 V and no internal short circuit had occurred was evaluated as ◯, and the rest were evaluated as ×.
[0047] Example 2 In Example 2, a magnesium alloy containing 9% by weight of lithium was used as the electrode, a glass filter (GA-200 manufactured by Advantech) having the thickness and air permeability shown in Table 1 was used as the separator, and a constant current test was performed in a symmetrical cell using an electrolyte solution of Mg(TFSA)2 / G2 with LiBH4 added as an additive, and a laminate exterior body. [Table 1]
[0048] Example 3 In Example 3, a polyethylene separator having a thickness and air permeability shown in Table 1 was used as the separator. The configuration other than the separator was the same as in Example 2. The test method was the same as in Example 2 under the same conditions.
[0049] Example 4 In Example 4, a polyethylene separator having a thickness and air permeability shown in Table 1 was used as the separator. The configuration other than the separator was the same as in Example 2. The test method was the same as in Example 2 under the same conditions.
[0050] Example 5 In Example 5, a polyethylene separator having a thickness and air permeability shown in Table 1 was used as the separator. The configuration other than the separator was the same as in Example 2. The test method was the same as in Example 2 under the same conditions.
[0051] Example 6 In Example 6, a polyethylene separator having a thickness and air permeability shown in Table 1 was used as the separator. The configuration other than the separator was the same as in Example 2. The test method was the same as in Example 2 under the same conditions.
[0052] Comparative Example 3 In Comparative Example 3, a polyethylene separator having a thickness and air permeability shown in Table 1 was used as the separator. The configuration other than the separator was the same as in Example 2. The test method was the same as in Example 2 under the same conditions.
[0053] Comparative Example 4 In Comparative Example 4, a glass separator having a thickness and air permeability shown in Table 1 was used as the separator. The configuration other than the separator was the same as in Example 2. The test method was the same as in Example 2 under the same conditions.
[0054] Comparative Example 5 In Comparative Example 5, a glass separator having a thickness and air permeability shown in Table 1 was used as the separator. The configuration other than the separator was the same as in Example 2. The test was performed under the same conditions as in Example 2.
[0055] Comparative Example 6 In Comparative Example 6, a glass separator having a thickness and air permeability shown in Table 1 was used as the separator. The configuration other than the separator was the same as in Example 2. The test method was the same as in Example 2 under the same conditions.
[0056] Comparative Example 7 In Comparative Example 7, a glass separator having a thickness and air permeability shown in Table 1 was used as the separator. The configuration other than the separator was the same as in Example 2. The test method was the same as in Example 2 under the same conditions.
[0057] Comparative Example 8 In Comparative Example 8, a glass separator having the film thickness and air permeability shown in Table 1 was used as the separator. The configurations other than the separator were the same as those in Example 2. The test was conducted under the same conditions as in Example 2.
[0058] As shown in Table 1, when the film thickness X satisfies 300 < X < 500 while the air permeability W is 110 or less (Comparative Example 3), the ionic conductivity becomes poor and the overvoltage increases. Also, when the air permeability W is 180 or more (Comparative Example 4), the strength of the separator becomes brittle and it no longer functions as a separator. Also, when the film thickness X is 300 or less (Comparative Examples 5 and 7), internal short circuit occurs. Further, when the film thickness X is 500 or more (Comparative Examples 6 and 8), the resistance component increases and the overvoltage becomes large. Therefore, by using the separators having the film thickness and air permeability of Examples 2 to 6, the thickness of the separator is ensured, and by having a high air permeability, the ionic conductivity is improved. Thus, even when using a magnesium alloy in the eutectic state, it is possible to suppress the occurrence of internal short circuit and reduce the overvoltage.
[0059] According to the magnesium ion secondary battery of the present invention, magnesium shows a reversible dissolution and deposition reaction, and a secondary battery that is electrochemically active can be obtained. Therefore, it can be used for various applications that require high output, such as a power stabilization power source.
Explanation of Reference Numerals
[0060] 1 Magnesium ion secondary battery 110 Case 111 Leaf spring 112 Positive current collector 113 Positive composite material layer 114 Separator 115 Negative electrode 116 Gasket 117 Cap 118 Positive electrode
Claims
1. A positive electrode and a negative electrode having a magnesium layer made of a eutectic magnesium alloy; A separator; Equipped with In the separator, ISO air permeability W (mL / m 2 .Pa.s) is 110<W<180, The film thickness X (μm) is 300<X<500, A magnesium ion secondary battery comprising:
2. The magnesium alloy has a crystal structure in which a hexagonal close-packed structure and a body-centered cubic structure are in a eutectic state.
2. The magnesium ion secondary battery according to claim 1 .
3. The magnesium alloy contains lithium in the range of 6% by weight to 10.5% by weight.
3. The magnesium ion secondary battery according to claim 2 .
Citation Information
Patent Citations
Working car
JP1978004961A
Electrode material for electrochemical device
WO2020013328A1